Entwicklung des Vorlandes unter Überflutungsänderungen aufgrund des Klimawandels - Torres Valdebenito, Emilio (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2019)
The purpose of this dissertation is to determine the effects of climate change on floodplains through changes in hydraulic conditions within these areas. It focuses on a case study situated in the Lower Saxonian Elbe Valley Biosphere Reserve, North Germany. The research deals with floodplains because of their sensitivity to variations in water levels, which will likely be severely influenced by climate changes. These concerns demand an investigation that first analyzes the physical fluvial processes and floodplains affected by changes in water level, and then - in response to the results obtained from the investigation - propose a methodology for analyzing the future development of floodplains. In order to undertake this research, a preliminary discussion of climate change and the difficulties in achieving resilient projections on future dimensions of climate variations is presented. Once the discussion on climate change has been reviewed, research focuses on the interactions between discharge, vegetation and sediments, the conditioning factors of fluvial morphodynamics. Another focal point is the investigation of mathematical tools, i.e. mathematical models that enable the analysis of future behavior of the riverbanks. Through this research the advantages of establishing one-dimensional modeling to predict the development of the river and floodplains are established. The investigation in the first part of the dissertation considers that the behavior of the riverbanks and floodplains results from the interaction between fluvial morphology and the morphology of floodplains, as well as variations in the distribution of vegetation. Such interactions ultimately determine future water levels and thus, also, the hydraulic conditions in that area. A methodology called "Dynamic Interaction of Models" is proposed for the analysis of future behavior of floodplains caused by climate change. This methodology predicts the evolution of floodplains as a result of interactions between fluvial morphology, morphology of floodplains and variations in the distribution of vegetation. Three one-dimensional models are used to make this forecast, which project the behavior of fluvial morphology, floodplains and distribution of vegetation. The influence of climate change is considered through varying discharges in the fluvial model, in the sediment transport model and in the soil water movement model, as well as in the analysis of changes in vegetation. In addition, future rainfall projections from regional climate models (REMO) are incorporated, using a variation of the ARMA stochastic model developed in this dissertation. The parameters und factors obtained through the various models were linked to each other in order to predict future water levels and flooding and thus the new hydraulic conditions for the floodplains. In the second part of this dissertation, the proposed methodology "Dynamic Interaction of Models" was applied in a case study. For this, two measuring stations on the Elbe River in Lower Saxony at river km 511, and km 515 were installed. These stations were also used for the KLIMZUG-NORD project. Over a period of 2 years, these measuring stations enabled the collection of more than 300,000 individual data of climate parameter, groundwater level, soil parameter and flooding level on the Elbe River in Lower Saxony at river km 511, and km 515. This information was important for the modeling of the future development of the floodplain (2012-2050) of a regulated stretch of the Middle Elbe River. The dissertation first details the relevant characteristics of the investigated area and then establishes the necessary materials and methods for the analysis of the future development of the floodplain in this area. The fluvial morphology was modeled for the period 2001-2100, as possible variations in shorter modeled periods would make the recognition of trends difficult. The corresponding models (e.g. river flow model, sediment transport model) are calibrated using collected field data, literature data, weather data from DWD stations, projected data from REMO, data from the hydraulic atlas of Germany, discharge data from Neu Darchau gauging station (Elbe-km 536,4), data of suspended sediments from Waterways and Shipping Office (WSA), and data of water temperature from ARGE-ELBE and the digital terrain model (DTM). Regarding the estimates of future flows, obtained by the ARMA-Variation stochastic model, which uses data from regional climate models, predicted values are compared with the results obtained from the BfG models (simulations of discharge between 1960 and 2099 in the context of research project KLIWAS - Impacts of Climate Change on Waterways and Navigation) in order to address the issue of diverse climatic projections. The dissertation concludes by highlighting the application and importance of the proposed method for the analysis of future development of floodplains of other rivers and regions out of or within Western Europe.

Das Ziel der vorliegenden Dissertation ist es, die Auswirkungen des Klimawandels auf die Entwicklung des Vorlandes als Ergebnis der sich ändernden hydraulidschen Bedingungen zu untersuchen. Die Untersuchung beschäftigt sich mit der Entwicklung des Vorlandes, da dieses Gebiet stark abhängig von Wasserstandsänderungen ist. Diese werden möglicherweise durch Klimawandel verstärkt und können folglich die zahlreichen Funktionen des Vorlandes beinträchtigen. Diese Problematik erfordert die Durchführung einer Untersuchung, die zunächst die durch die Variationen der Wasserstände betroffenen physikalischen Prozesse im Fluss und in den Flussauen analysiert und anschließend eine Methodologie für die Analyse der zukünftigen Entwicklung des Vorlandes herleitet. Beispielhaft wurde ein Bereich an der unteren Mittelelbe in Niedersachsen, Norddeutschland für die Untersuchung ausgewählt. Zu diesem Zweck befasst sich die Untersuchung im ersten Teil mit der aktuellen Diskussion über den Klimawandel und mit den bestehenden Schwierigkeiten, zu einer belastbaren zukünftigen Prognose des Ausmaßes der klimatischen Veränderungen zu gelangen. Anschließend konzentriert sich die Untersuchung auf die Interaktionen zwischen Abflüssen, Vegetation und Sedimenten, die die Flussmorphodynamik bedingen. Ein weiterer Schwerpunkt dieser Arbeit ist die Untersuchung der mathematischen Modelle, die eine Analyse des zukünftigen Verhaltens des Vorlandes ermöglichen. Mithilfe dieser Untersuchung werden die Vorteile der eindimensionalen Modellierung für die Prognose der Entwicklung dieses Gebiets deutlich. Die Untersuchung im ersten Teil der Dissertation führt zur Erkenntnis, dass sich das Verhalten des Vorlandes aus der Interaktion zwischen Fluss- und Flussauenmorphologie und der Auenvegetation ergibt. Diese Interaktionen bestimmen letztlich die zukünftigen Wasserstände und somit die hydraulischen Bedingungen für diese Zone. Für die Analyse des zukünftigen Verhaltens des Vorlandes unter Einfluss des Klimawandels wird eine Methodologie vorgeschlagen, die als Dynamische Interaktion von Modellen bezeichnet wird. Der Einfluss des Klimawandels wird durch die Variation von Abflüssen im Flussmodell, im Sedimenttransport- und Bodenwasserbewegungsmodell sowie bei der Analyse von Veränderungen der Vegetation berücksichtigt. Dazu werden die durch regionale Klimamodelle prognostizierten zukünftigen Niederschläge in die Berechnung der zukünftigen Abflüsse durch eine in dieser Dissertation entwickelten Modifikation des stochastischen Modells AutoRegressive-Moving-Average (ARMA) eingeschlossen. Die ausgearbeiteten Entwicklungsprognosen der verschiedenen Modelle werden miteinander verknüpft, um zukünftige Wasserstände und Überflutungen und damit die neuen hydraulischen Bedingungen für das Vorland zu prognostizieren. Im zweiten Teil dieser Dissertation wird die vorgeschlagene Methodologie der Dynamischen Interaktion von Modellen in einem Fallbeispiel angewandt. Dafür wurden zwei Messstationen an der Elbe zwischen Elbe-km 511 und 515 installiert, die auch im Rahmen des Projekts KLIMZUG-NORD verwendet wurden. Diese Messstationen ermöglichten innerhalb von 2 Jahren die Erhebung von mehr als 300.000 Felddaten. Diese Informationen erlauben es, die Entwicklung des Vorlandes (2021-2050) in einer regulierten Flussstrecke der Elbe (Mittelelbe) zu prognostizieren. Dazu werden zunächst die bedeutenden Charakteristika des Untersuchungsgebiets dargestellt und nachfolgend Material und Methoden erläutert, die für die Analyse der Entwicklung des Vorlandes im Untersuchungsgebiet erforderlich sind. Die Flussmorphologie wird für den Zeitraum 2001-2100 modelliert, da eine Tendenz bei möglichen Variationen in einem kurzen Zeitraum nur schwer wahrgenommen werden kann. Die jeweiligen Modelle werden u.a. mithilfe erhobener Felddaten, Daten aus der Literatur, Klimadaten aus den Stationen des Deutschen Wetterdiensts (DWD), projizierten Daten des regionalen Klimamodells REMO, Daten des hydrologischen ATLAS von Deutschland, Abflussdaten des Pegels Neu Darchau (Elbe-km 536,4), Geschiebe-Schwebstoffdaten des Wasser- und Schifffahrtsamts (WSA) und der Bundesanstalt für Gewässerkunde (BfG), Wassertemperaturdaten der Arbeitsgemeinschaft für die Reinhaltung der Elbe (ARGE-ELBE) und das Digitale Geländemodell (DGM) kalibriert. Die durch das stochastische Modell ARMA/Variation erhaltenen Berechnungen der zukünftigen Abflüsse, die die Prognose der regionalen Klimamodelle berücksichtigen, werden mit den durch die BfG-Modelle erhaltenen Ergebnissen verglichen, um die Problematik der Vielfalt von klimatischen Prognosen anzugehen. Schließlich werden in dieser Dissertation die Anwendung und Bedeutung der vorgeschlagenen Methodologie für die Analyse der Entwicklung des Vorlandes anderer Flüsse und Regionen außerhalb Mitteleuropas behandelt.
The impact of climate change on floodplain development: a case study from the Lower Saxonian Elbe River Biosphere Reserve (Wehninger Werder)
Fallbeispiel Wehninger Werder im Biosphärenreservat Niedersächsische Elbtalaue
Keywords: Climate Change; Biosphere Reserve; Klimawandel; Biosphärenreservat; 914.3 Landeskunde Deutschlands